Prevalencia de infección de la vía urinaria y perfil microbiológico en mujeres que finalizaron el embarazo en una clínica privada de Lima, Perú - Quirós-Del Castillo, Ana Lucía (2018)
ABSTRACT Objective: To describe the prevalence of urinary tract infections (UTI) and their microbiological profile in pregnant women attended in a private clinic of level II-2 of Lima, Peru. Materials and methods: An analytical cross-sectional observational study was conducted, in women they had their delivery in a private clinic during January 2016 to December 2017. Inclusion criteria were those who had at least 06 prenatal care. Results of urocultures and their respective antibiotic resistance were obtained. In the statistical analysis, central tendency measures such as averages, standard deviation and frequencies were found. Results: 1455 met the selection criteria. We found 108 patients (7.4%) with UTI with a positive urine culture. The 70 cases (63.6%) were Escherichia coli resistant to antibiotics such as: ampicillin (57.6%), ciprofloxacin (30.7%) and norfloxacin (30.7%), and sensitive to: amikacin, nitrofurantoin and cefuroxime. However, was is found that 13 (11.8%) had Escherichia coli BLEE resistant to cephalosporins. Conclusion: The prevalence of urinary infection was within what was expected in relation to international reports. The most commonly isolated uropathogen was Escherichia coli, followed by Escherichia coli BLEE.